2022
DOI: 10.1175/jas-d-21-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Model of Tropical Cyclone Central Pressure Filling at Landfall

Abstract: We derive a simple physically based analytic model which describes the pressure filling of a tropical cyclone (TC) over land. Starting from the axisymmetric mass continuity equation in cylindrical coordinates we derive that the half-life decay of the pressure deficit between the environment and TC centre is proportional to the initial radius of maximum surface wind speed. The initial pressure deficit and column-mean radial inflow speed into the core are the other key variables. The assumptions made in deriving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…We derive a simple but useful new model of pressure tendency. Sparks and Toumi (2022) applied mass continuity in cylindrical coordinates to relate average pressure changes within a given radius to column radial wind speeds at that radius (Equation 1). From here our new model diverges.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We derive a simple but useful new model of pressure tendency. Sparks and Toumi (2022) applied mass continuity in cylindrical coordinates to relate average pressure changes within a given radius to column radial wind speeds at that radius (Equation 1). From here our new model diverges.…”
Section: Discussionmentioning
confidence: 99%
“…Sparks and Toumi (2022) modeled the TC as an axisymmetric vortex, considering only horizontal motion, and showed that the tendency of the average surface pressure within a cylinder of radius r can be written as, P(r)t=2P(r)scriptVr(r)r. $\frac{\partial \langle P(r)\rangle }{\partial t}=-\frac{2P(r){\mathcal{V}}_{r}(r)}{r}.$ where P is the surface pressure with angled brackets denoting the areal average within radius r and scriptVr ${\mathcal{V}}_{r}$ is the density‐weighted column mean radial wind velocity. In the vicinity of the inner core, scriptVr ${\mathcal{V}}_{r}$ is positive (directed away from the center) for intensification and negative for TC decay.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations